(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. The learners experience stress and anxiety at school because of bullying, and routine stressors are perceived as the dangerous ones. Therefore, they even do not want to go to school. Young learners’ psychological well-being and self-esteem is good, and the children experience positive emotions in physical education lessons. Research aim. The aim of the research was to analyze young learners’ self-esteem and psychological well-being in physical education classes. Research methods. Young learners’ self-esteem and psychological well-being in physical education lessons were analyzed in Klaipėda city schools using an anonymous questionnaire survey method. Research results. Summarizing the research results of learners’ psychological well-being, it can be noted that psychological well-being of 41.0% of learners in physical education lessons was good or very good. Analysis of the results of young learners’ self-esteem in physical education lessons showed that 41.0% of learners estimated themselves as the average ones. Discussion and conclusions. Although young learners like attending physical education lessons, and they find the lessons easy, interesting, pleasant, good and useful, they feel unsafe in physical education lessons because they suffer from other children’s bullying. There were cases when they did not want to go to physical education lessons at all. Keywords: bullying, stress and anxiety, reluctance to go to school.